Consumo de antimicrobianos de uso restringido en el servicio de UCI-adulto del Hospital de Alta Complejidad Virgen de la Puerta (HACVP) -EsSalud, julio- diciembre 2016 - Peña Juarez, Yajayra Yolanda (2017)
The present study has for aim determine the consumption of antimicrobial of restricted use expressed in DDD/100 beds / day in the UCI-adult's service of Alta ComplejidadVirgen's Hospital of the Door (HACVP)-EsSalud, in July - December, 2016. For which the antimicrobial ones of restricted use evaluated were those who think inside the Special Medicines that They Need Supervision (MERS) particularly 5 were studied only: capofungina, ertapenem, colistina, tigeciclina and linezolid, that are the antimicrobial ones most used and consumed by unit of intensive care (UCI) - adult. There was realized a retrospective - descriptive study of transverse court in the antimicrobial ones of restricted use, in which it included the patients hospitalized in unit of intensive care (UCI) - adult during the period of July - December, 2016. In the results is observed, that the antimicrobial one of major consumption of units in UCI-adult was caspofungina 50 mg with road 176 followed of linezolid with 174 road ones and of minor consumption it was ertapenem with road 5. The major expressed consumption DDD/100camas/día was caspofungina 50mg with 10,24 DDD/100camas/día, is interpreted that by every 100 beds approximately 10 patients get caspofungina of 50mg in UCI-adult. The antimicrobial one of use restricted of major economic expense was the caspofungina of 50 mg with S/.235029 followed by the caspofungina of 70mg with S/.65462 .En the study one concludes, that the caspofungina of 50mg is the antimicrobial one of major rotation and of major consumption with 10,24 DDD/100camas/día and that of major economic cost in UCI-adult.